Personality development through yoga practice is the foundation of a self-realized life - Indu Sharma; Pavan Kumar (Dr. Chinmay Pandya, 2024)
Personality is the dynamic conjunction of mental and physical qualities by which an individual harmonizes with his external environment. Different dimensions i.e., physical, mental, spiritual, social etc. affect it. Psychologists believe that personality is worth studying. It is a fact that by developing the different dimensions as mentioned, a person can enrich in superior personality. In this, Yoga Vidya, the heritage of Indian culture, proves effective in the form of an important means. Yoga Vidya, by improving the way of living life, behavioral traits and by uplifting the spiritual level is an effective method of making positive changes in personality. The objective of the presented research work is to understand the effect of Yoga Vidya on different dimensions of personality, so that by self-development, a person can be successful in uplifting himself and the nation. In the first part of the research, the introduction of personality and its psychological and Yogic aspect have been explained. In the second part, giving introduction to yoga, an attempt has been made to explain the effect of yoga practices on personality, for which the facts and concepts of all-round personality development propounded by Upanishads, Darshana, Gita etc. have been included. The research work ends with the conclusion that personality development is possible through yoga and a developed personality is the key to become self-reliant, which is the foundation of self-reliant India. A well-developed personality plays an important role in the progress of the country.